Mungkinkah Stres Kerja Memediasi Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Hotel “T” Di Kota Probolinggo - Hermanto, Hermanto; Mutinda Teguh Widayanto; Leliya Nanda Tiyas Sinta Devie (RELASI : JURNAL EKONOMI, 2024)
The purpose of this study, which was done in the “T” Hotel in Probolinggo City, is to examine how job stress is a mediator between employees' workloads and the quality of their work. Workload, Work Environment, and Work Stress are exogenous (independent) factors in this descriptive quantitative study, whereas Employee Performance is an endogenous (bound) variable. The data in this study were collected using interviews, documentation, and questionnaires, with a population of 32 respondents using the census method. Information obtained from: 1. Source material; 2. Information Gathered From Other Sources. Path analysis testing approaches are used as part of a structural equation model (SEM) with the use of SmartPLS version 4 software. According to the findings, there is some positive but not statistically significant correlation between workload and performance, some positive but statistically significant correlation between workload and performance mediated by work stress, some positive but statistically significant correlation between workload and performance, and some positive but statistically significant correlation between workload and performance “